Effect of prey concentrations and feed training on production of Hoplias lacerdae juvenile - Luz, Ronald K.; Portella, Maria Célia [UNESP] (Academia Brasileira de Ciências, 2015)
The aim of this work was to investigate the s of daily prey concentration during the first 15 days of active feeding of Hoplias lacerdae larvae, and the juvenile size on the feed training. In the first phase, the larvae received five Artemia nauplii concentrations (P). In the second phase, the juveniles from each treatment were trained to accept formulated diet. Superior growth was related to higher initial daily prey concentrations (900 and 1100 nauplii larvae-1). During feed training, the growth tendency was similar to that verified in the first phase. The lowest values of specific growth rate (SGR) were registered after the introduction of the semi-moist diet used in the feed training. However, the values of SGR recovered along the experiment and similar rates were found among the treatments. Survival, mortality and cannibalism were similar in the different treatments at the end of both phases. It can be concluded that: the prey concentration affects growth of H. lacerdae during the first 15 days of active feeding, and feed training can be initialized with juveniles of about 16 mm of total length.

O objetivo deste trabalho foi avaliar o efeito de diferentes concentrações de presa durante os primeiros 15 dias de alimentação ativa de larvas de Hoplias lacerdae e o tamanho inicial dos juvenis no condicionamento alimentar. Na primeira fase as larvas receberam cinco concentrações de náuplios de Artemia (P). Na segunda fase, os juvenis de cada tratamento foram condicionados a aceitar dieta formulada. Maior crescimento foi verificado nas mais altas concentrações iniciais diárias de presa mais altas (900 e 1.100 náuplios por larva). Durante o condicionamento alimentar a tendência de crescimento foi semelhante à registrada na primeira fase. As taxas de crescimento específico (TCE) mais baixas foram verificadas com o início do fornecimento da dieta semi-úmida usada no condicionamento alimentar. No entanto, os valores das TCE mostraram recuperação no decorrer do trabalho e valores similares foram encontrados entre os tratamentos. A sobrevivência, mortalidade e canibalismo foram semelhantes entre os diferentes tratamentos ao final das duas fases. Pode-se concluir que: a concentração de presas afeta o crescimento de H. lacerdae durante os primeiros 15 dias de alimentação ativa e o condicionamento alimentar pode ser iniciado em juvenis com comprimento total de aproximadamente 16 mm.
Keywords: Artemia; Feeding management; Larviculture; Formulated diet; Artemia; Manejo alimentar; Larvicultura; Dieta formulada